Comparative Study Gallbladder Contractility Index Using Ultrasound in Patients with and without Liver Cirrhosis - Hari Soekersi; Leni Santiana; Fetty Fatmawaty (Universitas Islam Bandung, 2020)
Liver cirrhosis leads to impairment of gallbladder contractility resulting in bile stasis and facilitate the development of gallstones that will aggravate the clinical symptoms of the patients. The gallbladder contractility index is an indicator of gallbladder motility measured using ultrasound as the radiological choice of modality. This study aims to determine differences in the gallbladder contractility index using ultrasound in patients with and without liver cirrhosis. This study was an observational study of comparative analytic with cross-sectional design with sampling conducted by consecutive admissions sampling at Dr. Hasan Sadikin General Hospital Bandung from December 2017 to February 2018. Statistical analysis than performed by using an independent t test to find out the difference of gallbladder contractility index in patients with and without liver cirrhosis. A total of 22 subjects, 12 men, 10 women, with the youngest 37 years old and the oldest 70 years old. The result of the study was obtained mean fasting gallbladder volume (35.56±22.16 mL) and postprandial (21.25±16.08 mL) in patients with liver cirrhosis higher than without liver cirrhosis with mean fasting gallbladder volume (16.50±4.14 mL) and postprandial (5.44±2.10 mL). The average gallbladder contractility index on patients with liver cirrhosis (41.64±24.52%) smaller than without liver cirrhosis (66.73±9.19%). The result of the statistical test showed that there was a significant difference in the gallbladder contractility index on patients with liver cirrhosis than without liver cirrhosis (p=0.007, p≤0.05). In conclusion, there was a significant difference in the gallbladder contractility index that measured by using ultrasound between the patients with and without liver cirrhosis. PERBEDAAN INDEKS KONTRAKTILITAS KANDUNG EMPEDU MENGGUNAKAN ULTRASONOGRAFI PADA PENDERITA SIROSIS HATI DAN TANPA SIROSIS HATISirosis hati menyebabkan gangguan indeks kontraktilitas kandung empedu yang mengakibatkan stasis cairan empedu dan memudahkan kejadian batu empedu yang akan memperberat gejala klinis pasien. Indeks kontraktilitas kandung empedu merupakan indikator motilitas kandung empedu yang diukur menggunakan ultrasonografi (USG) sebagai modalitas pilihan radiologi. Penelitian ini bertujuan mengetahui perbedaan indeks kontraktilitas kandung empedu menggunakan ultrasonografi pada pasien sirosis hati dan tanpa sirosis. Penelitian ini menggunakan studi observasional analitik komparatif dengan rancangan cross-sectional dan pengambilan sampel dilakukan secara consecutive admissions sampling di RSUP Dr. Hasan Sadikin Bandung dari bulan Desember 2017 hingga Februari 2018. Uji statistik menggunakan independent t test. Subjek penelitian berjumlah 22, laki-laki 12 dan perempuan 10, serta usia termuda 37 tahun dan tertua 70 tahun. Hasil penelitian didapatkan volume rerata kandung empedu puasa (35,56±22,16 mL) dan pascaprandial (21,25±16,08 mL) pada pasien sirosis hati lebih besar daripada tanpa sirosis hati dengan volume rerata kandung empedu puasa (16,50±4,14 mL) dan pascaprandial (5,44±2,10 mL). Indeks kontraktilitas rerata kandung empedu penderita sirosis hati (41,64±24,52%) lebih rendah dibanding dengan tanpa sirosis hati (66,73±9,19%). Hasil uji statistik menunjukkan terdapat perbedaan bermakna antara indeks kontraktilitas kandung empedu penderita sirosis hati dan tanpa sirosis hati (p=0,007; p≤0,05). Simpulan, terdapat perbedaan bermakna antara indeks kontraktilitas kandung empedu menggunakan USG pada penderita sirosis hati dan tanpa sirosis hati.